2015
DOI: 10.3732/apps.1500058
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation at microsatellite loci in the tropical herb Aphelandra aurantiaca (Acanthaceae)

Abstract: Premise of the study:To assess the effect of forest fragmentation on genetic variation and population structure of Aphelandra aurantiaca (Acanthaceae), a tropical and ornamental herbaceous perennial plant, we developed the first microsatellite primers for the species.Methods and Results:Fourteen microsatellite markers were isolated and characterized from A. aurantiaca genomic libraries enriched for di-, tri-, and tetranucleotide repeat motifs. Polymorphism was evaluated in 107 individuals from four natural pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…Similarly, Geng et al [ 45 ] calculated the observed and expected heterozygosity in Acanthus ilicifolius using SSR markers, which ranged from 0.200 to 0.875 and 0.227 to 0.798, respectively. Furthermore, Suárez-Montes et al [ 46 ] also calculated the observed and expected heterozygosity values among the Aphelandra aurantiaca genotypes, ranging from 0.22 to 0.96 and 0.20 to 0.87, respectively, which is higher than the present study. The present investigation also deciphered large differences between the observed and expected heterozygosity, which indicates that the selected population of A. paniculata deviates from Hardy Weinberg’s equilibrium, which might be due to inbreeding, population bottleneck, or random genetic drift [ 17 , 45 ].…”
Section: Resultscontrasting
confidence: 77%
“…Similarly, Geng et al [ 45 ] calculated the observed and expected heterozygosity in Acanthus ilicifolius using SSR markers, which ranged from 0.200 to 0.875 and 0.227 to 0.798, respectively. Furthermore, Suárez-Montes et al [ 46 ] also calculated the observed and expected heterozygosity values among the Aphelandra aurantiaca genotypes, ranging from 0.22 to 0.96 and 0.20 to 0.87, respectively, which is higher than the present study. The present investigation also deciphered large differences between the observed and expected heterozygosity, which indicates that the selected population of A. paniculata deviates from Hardy Weinberg’s equilibrium, which might be due to inbreeding, population bottleneck, or random genetic drift [ 17 , 45 ].…”
Section: Resultscontrasting
confidence: 77%
“…DNA extraction, amplification, and laboratory setup are detailed in Suárez-Montes, Tapia-López & Núñez-Farfán (2015). We genotyped all sampled individuals and scored alleles using the software GeneMarker V.2.4.0 (SoftGenetics, State College, PA, USA).…”
Section: Microsatellites Analysis and Pcr Amplificationmentioning
confidence: 99%
“…Manuscript to be reviewed individual plants (Table 3). To estimate the outcrossing rate (t) and pollen pool structure ) (ф we used six highly polymorphic unlinked microsatellite loci (0432, 5409, 1233, 4536, 4483, and 1808) (Table S2) (Suárez-Montes, Tapia-López & Núñez-Farfán, 2015) and analyzed the members of the maternal families (6 to 10 families per population).…”
Section: Mating System and Contemporary Gene Flowmentioning
confidence: 99%